SYSTEMATIC PHYSICAL ACTIVITY IN HEALTH PROMOTION AND DISEASE PREVENTION - Czarnecki, D.; Skalski, D. W.; Rybak, L.; Kindzer, B.; Graczyk, M.; Orel, I. (Rehabilitation and Recreation, 2022)
Everyone looks forward to good weather, which, together with spending time outdoors, promotes physical activity. Movement is meant to bring relaxation and pleasure. If you are healthy, you can prepare a set of recreational activities yourself. However, it is worth remembering that cooperation with an instructor increases the safety of the exercises. It should be remembered that possible forms of physical activity depend on individual characteristics: age, bone condition or diseases. Nevertheless, it is needed at all stages of life, especially in adolescence, when it affects the modeling and adaptive changes in bones. In adults, it increases bone mineral density. On the other hand, in the elderly, muscle wasting reduces mechanical bone stimulation and leads to their malfunction, and consequently to micro-injuries and fractures. Hence, undertaking appropriately selected forms of physical activity is also advisable. Nowadays, mental overload, stress, unhygienic lifestyle and movement deficit are the cause of many ailments, generally referred to as civilization diseases, which include: coronary artery disease, arterial hypertension, strokes of the brain, diabetes, degenerative spine disease, obesity, etc. Systematic physical activity turns out to be a beneficial preventive action in the prevention of many of them. Physical activity has been considered very beneficial for health for years. Undoubtedly, it also plays a very valuable role in well-being – during physical activity and sports, hormones that are beneficial for health and good mood are produced, which stimulate all physiological processes in the body, improve the mood and, among other things, affect the immune system and the functioning of the immune system. Undoubtedly, there are many advantages to regular physical activity, so it is worth including systematic effort and sport in your everyday life. Please note that if you are seriously ill, please consult your physician before starting physical activity.